Manuel Bandeira entre o sagrado e o profano - Almeida, Maria Cecilia Pimentel de Castro Pinto (2014)
This work is about recurrent themes in Manuel Bandeira s poetry such as tuberculosis, childhood and religiosity. In three chapters, each of them concerned with the subjects previously mentioned, we tried to study Bandeira s lyrical poetry not only under MirceaEliade theories, but also from some thoughts collected from Aristóteles, MassaudMoisés, Alfredo Bossi, Affonso Romano de Sant Anna, Victor Manuel de Aguiar e Silva whose texts would evoke a better understanding of the poetry of the author of Libertinagem . The first chapter is about Manuel Bandeira s poetry as a kind of cosmogony process through which the lyrical self tries to neutralize the consequences of a bad destiny which had transformed his life on a true chaos; in the second chapter we tried to verify to what extent the poems about childhood highly charged by escape feelings tried to reconstruct, through the sortilege of language, a mythological and paradisiacal territory to neutralize the effects of reality that oppressed him so much. It is worth mentioning that the valuable poems about childhood provided us with other important considerations. In the last chapter, the main focus was on the erotic bias of Bandeira s religious poetry and on the way the lyrical self desecrates the sacred at the same time it makes the profane sacred by giving an erotic touch to the saints like in the poem Balada de Santa Maria Egipcíaca , or by sacralizing humble and anonymous human beings who seems to be accomplishing a true via crucis on earth.